A Systematic Review of Knowledge, Attitude and Practice on Adverse Drug Reactions and Pharmacovigilance among Doctors - Abdullahi Rabiu Abubakar, Nordin Bin Simbak, Mainul Haque (Journal of Applied Pharmaceutical Science, 2014)
Background: Adverse drug reactions (ADRs) have been making headlines because of life threatening issues. ADRs are always underreported and still the major public health problem. Spontaneous reporting system has remained the most significant method for safeguarding patients’ lives. Objectives: Is to examine and analyse the various pharmacovigilance (PV) studies conducted among doctors and to make recommendations for future research. Study Selection: 32 studies covered from 2004 to 2014 were selected. Data Sources: Four electronic data-bases including Science-Direct, Springer-Link, PubMed and MEDLINE were used to obtain 129 relevant publications using HotBot, FreeFullPDF, and Google Scholar as search engines. Data Extraction: Studies conducted on doctors were selected covering research from ten countries. Inclusion Criteria: Only studies done from 2004 to 2014 were included, KAP studies done on ADRs and pharmacovigilance among doctors were selected. Exclusion criteria: All studies done before 2004 and studies done on general public KAP were excluded; similarly, studies conducted on healthcare professionals in general were excluded; also studies done on adverse drug event (ADE) reporting were excluded. The study was conducted from April to August, 2014. Data Synthesis: Knowledge, attitude and practice (KAP) regarding ADRs reporting by doctors were poor. Longitudinal study involving educational intervention and training through workshops and seminars were found to be effective in improving doctors’ knowledge and attitude. Conclusion: There is urgent need to improve knowledge, awareness and practice of doctors on pharmacovigilance. It is imperative for WHO and national pharmacovigilance centres to take proactive measures to curve the menace of ADRs in order to safeguard the patients’ lives. The curriculum of all health and health related schools should be restructured with respect to pharmacovigilance without any delay and hesitation.
Keywords: Adverse Drug Reactions,Pharmacovigilance,Knowledge,Attitude,Practice.